2018
DOI: 10.1186/s12913-018-3225-4
|View full text |Cite
|
Sign up to set email alerts
|

Why not? Understanding the spatial clustering of private facility-based delivery and financial reasons for homebirths in Nigeria

Abstract: BackgroundIn Nigeria, the provision of public and private healthcare vary geographically, contributing to variations in one’s healthcare surroundings across space. Facility-based delivery (FBD) is also spatially heterogeneous. Levels of FBD and private FBD are significantly lower for women in certain south-eastern and northern regions. The potential influence of childbirth services frequented by the community on individual’s barriers to healthcare utilization is under-studied, possibly due to the lack of suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Although the area's energy sector has generated interest among multi-national companies [71], most Bayelsans remain poor, while the state's public infrastructure is underdeveloped [72,73]. The proportion of women in Bayelsa who cited financial reasons for homebirth is higher than the national average [74]. Under such special economic and environment conditions, wealth may be additionally helpful for overcoming cost of transport, as well as trade-offs in time and financial loss from daily/productive activities.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Although the area's energy sector has generated interest among multi-national companies [71], most Bayelsans remain poor, while the state's public infrastructure is underdeveloped [72,73]. The proportion of women in Bayelsa who cited financial reasons for homebirth is higher than the national average [74]. Under such special economic and environment conditions, wealth may be additionally helpful for overcoming cost of transport, as well as trade-offs in time and financial loss from daily/productive activities.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Use of emergency caesarean section depends on the availability of services that are of sufficient quality. In many rural settings in Nigeria, there are no health facilities [40], and in areas where they exist, the quality of services available is poor, with a lack of consistent supplies, equipment and human resources, especially doctors [21, 4145]. The problem is further exacerbated by insufficient referral systems and lack of a functioning ambulatory system or a quick alternate transport system [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…In 22 countries, the trend in the poorest quintile was also increasing except in Nigeria and Cameroon where it was decreasing; and stalling in Mozambique. In other countries such as Nigeria, the increased home deliveries among the poorest women in areas of high private sector delivery may suggest a preference to avoid public sector facilities where private sector delivery is unaffordable [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons include disincentives to use traditional birth attendants at home (eg, in Malawi) [46,47]; increased awareness of the benefits of facility-based delivery [13]; and women’s ability to negotiate use of health services [48,49]. Other studies have also reported that for-profit health care may be more appealing due to a number of reasons such as privacy, shorter waiting times, the quest for high quality of care, availability of doctors and as a symbol of status [37]. The increased number of facility births observed since 2000 provides countries with daunting challenges such as strengthening the generally weak health systems and implementing robust health financing structures, particularly in settings where out of pocket health expenditures are high.…”
Section: Discussionmentioning
confidence: 99%